Numerical Study of Confined Explosions in Urban Environments - Codina, Ramon Humberto (2013)
In recent years, events such as the attack on the World Trade Center as well as many other attacks around the world have shown that terrorism related activity is dramatically increasing. Such a situation makes necessary to study the effects of blast loading on complex urban environments. In this paper, the phenomenon of channelling in congested urban environments is studied. Channelling is a phenomenon that can significantly increase the destructive potential of a shock wave of an explosion. Hence, channelling must be taken into account in the design of structures subjected to extreme loads in congested urban environments. This paper presents a novel approach to understanding channelling effects using maps of overpressure amplification and impulse amplification. These maps are developed for different street widths and amounts and locations of explosive loads and could be used as a first approximation for design purposes. The characteristic channelling zones are defined and characterised for the first time in the open technical literature. Finally, quantitative conclusions about the influence of the different parameters are highlighted.